A Legal Analysis of the Unilateral Termination of Labor Contracts and Noteworthy Points for Mitigating Related Disputes - Truong, Phung Van; Thuy Lam, Tran Thi; Quynh, Nguyen Dieu; Phuc, Bui Minh (VNU Journal of Science: Legal Studies, 2024)
The Labor Code of the Socialist Republic of Vietnam was first promulgated in 1994 and was subsequently revised in 2002, 2006, and 2007. The economic and social conditions and labor relations have evolved, necessitating prompt amendments to labor legislation, resulting in the issuance of the Labor Code 2012. However, after five years of application, the 2012 Labor Code has revealed many deficiencies affecting employees' legal rights and interests, including the conditions that employees must meet when they wish to unilaterally terminate the labor contract; these conditions are considered very difficult to prove in the position of an employee. The Labor Code 2019 was enacted with several enhancements, including the elimination of regulations pertaining to unilateral conditions for employees, thereby safeguarding their right to select better employment opportunities and preventing and combating coerced labor. In this article, the author analyzes current law on unilateral termination of labor contracts, focusing on the legal aspect, and selects some common dispute practices related to unilateral termination of labor contracts that businesses and individuals should be aware of to protect their mutual legal rights and interests, as well as those of both parties.